PROBLEMS OF LENDING TO MICRO-ENTERPRISES IN UKRAINE UNDER THE CONDITIONS OF MARTIAL LAW (World of finance, 2023)
Introduction. As a result of the full-scale war with the Russian Federation, micro-enterprises in Ukraine have been negatively affected by factors related to the hostilities, which have led to a deterioration in their financial and economic condition and an increase in credit risks, which limited access to bank lending for micro-businesses. Given the prolongation of the war and the gradual decline in the purchasing power of the population, micro-enterprises will need state credit support to preserve their businesses and create conditions for their development during the post-war reconstruction period. Therefore, in the theory and practice of bank lending to micro-enterprises, the issue of finding effective mechanisms for credit support for micro-businesses under martial law is becoming relevant.The purpose of the article is to investigate the problems of micro-business lending under martial law in Ukraine and to develop scientifically based proposals for improving the policy of bank lending to small enterprises.Results. The article analyzes current trends in bank lending to micro-enterprises in Ukraine under martial law. The author substantiates three groups of key problems that negatively affected the dynamics and timing of bank lending to micro-businesses, namely: ineffective monetary policy of the National Bank of Ukraine in the context of combating supply-side inflation; increased credit risks due to hostilities and deteriorating macroeconomic conditions; and gaps in the State program ‘Affordable Loans 5-7-9 %. Based on the assessment of the identified problems of bank lending to micro-enterprises in Ukraine, the paper substantiates measures to intensify it under martial law and given the need to develop the processing industry, production infrastructure, and support for family farming as a type of micro-business.Conclusions. The article proposes to solve the existing problems of micro-enterprise lending by revising the NBU's interest rate policy in the context of combating non-monetary inflation by monetary methods, which requires a reduction in interest rates, primarily on deposit certificates, to release funds for targeted lending to micro-businesses. The areas of micro-business lending under the existing state program ‘Affordable Loans 5-7-9’ also need to be expanded by targeting funds for the development of the processing industry, micro-business production infrastructure, and family farming, which will ultimately increase the level of local economic development, increase the number of jobs and ensure the well-being of the Ukrainian population.